2021
DOI: 10.1002/ente.202001076
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature and Rapid Deposition of an SnO2 Layer from a Colloidal Nanoparticle Dispersion for Use in Planar Perovskite Solar Cells

Abstract: Deposition of the electron transport layer (ETL) is an important step in the manufacture of low‐cost, solution‐processed perovskite solar cells (PSCs). Thermal annealing processes account for a major part of the energy consumption involved in the fabrication of PSCs. The current paper presents a plasma‐based and highly convenient method (5 min, <60 °C) for the deposition of SnO2 films (PT‐SnO2) from a colloidal nanoparticle dispersion. A comparative evaluation of PT‐SnO2 films with those created by state‐of‐th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The origin of HI in PSC is multifactored, as it can be attributed to either charge accumulation at the interface or other reasons, such as ion migration in MAPbI 3 . 7 Therefore, the low HI for LTP-SnO 2 is mainly due to the low charge accumulation at the interface of ETL/MAPbI 3 , as evidenced by previous TRPL results that show a low s avg value. It was also reported that the large grain size of MAPbI 3 also reduces HI.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The origin of HI in PSC is multifactored, as it can be attributed to either charge accumulation at the interface or other reasons, such as ion migration in MAPbI 3 . 7 Therefore, the low HI for LTP-SnO 2 is mainly due to the low charge accumulation at the interface of ETL/MAPbI 3 , as evidenced by previous TRPL results that show a low s avg value. It was also reported that the large grain size of MAPbI 3 also reduces HI.…”
Section: Resultsmentioning
confidence: 59%
“…[1][2][3][4][5][6] Generally, n-i-p planar structures are employed in most state-of-the-art PSCs where the perovskite light-absorbing layer is sandwiched between the ETL and HTL. 7 Appropriate selection of the ETL plays a dominant role in determining the performance of PSCs by effectively extracting and transporting photogenerated electrons from the perovskite layer to the electrodes. Recently, extensive research has been focused on metal oxide-based ETLs, such as TiO 2 , SnO 2 , ZnO, InO 3 , and Nb 2 O 5 , for planar structure-based PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Shekargofta et al deposited SnO 2 thin films with uniform and highly crystalline surfaces at 60 °C through Ar plasma treatment of spin-coated SnO 2 precursors. 80 Compared with the SnO 2 film treated by traditional thermal annealing, the surface of the SnO 2 film treated with Ar plasma is very smooth and pinhole-free. Most importantly, the stability of the PSCs based on Ar plasma-treated SnO 2 is better, maintaining 80% of the initial performance after 504 h under environmental conditions.…”
Section: The Preparation Methods Of the Sno2 Etlmentioning
confidence: 99%
“…For a faster annealing process, as is preferable in a R2R process, a 5 min long atmospheric pressure plasma can be used instead. 12 The air-knife was not required for this deposition.…”
Section: Papermentioning
confidence: 99%